Philippines : PPP Options in Irrigation Sector - World Bank (Washington, DC, 2014)
This study proposes an analytical framework to determine the extent to which Public-Private Partnership (PPP) is a viable and effective business option for developing and modernizing the irrigation sector in the Philippines. It focuses on: (a) assessing and providing recommendations to address the policy, regulatory and institutional constraints that limit the recourse to PPP as a tool to support the development of the irrigation sector; and (b) if PPP is proven to be a viable option, develop the capacity within the Department of Agriculture (DA), National Irrigation Administration (NIA) and National Economic Development Authority (NEDA) PPP Center to identify and assess potential projects. The TA was meant primarily to produce a simple and practical analytical framework for the Government to build on, rather than a full-blown study on an irrigation PPP project. Adopting the PPP scheme in irrigation will require specific answers to the following questions: (1) how PPP contractual arrangements can help to address the usual problems in public irrigation (e.g., maintenance problems due to budget restriction and decision making processes); (2) how PPP can ensure financial viability of the irrigation system; (3) how PPP can avoid political interference in setting irrigation fees; and (4) how PPP can increase the useful life of irrigation systems and break the vicious cycle of low collection of irrigation fees, poor maintenance, network degradation and expensive rehabilitation. The PPP scheme has to make the case that the financial costs of privately-funded projects are on a par with those of publicly-funded projects.